A Comparative Study of Foliar and Soil potassium Fertilizer on Growth and Yield of Strawberry Cultivated in Non-Heated Greenhouses - Chnoor Yousif Shkwr; Hawzhin Khalid; Nigar Majeed (Agricultural Science, 2022)
This study has been conducted in the non-heated greenhouse of the of  Protected  agriculture department of the Bakrajo Technical Institute of -Sulaymaniyah Governorate during winter season of  2019  The purpose of this study to determine the effect  of soil fertilization  and foliar application  of potassium   with different  rates  ( 0  as control , 1.5 , 2.5  and 3.gm/L ) on strawberry  cv.  Rubygem growth and yield. The parameters recorded  were  number of leaf  per plant, number of flower per plant, number of fruit per plant, weight of fruit  (gm), total acidity %  of fruit (T.A) and total soluble solid (TSS) of the fruit. According to the results of most of the parameters of this study the foliar application of the fertilizer (K) is better than applying the fertilizer of soil in most parameters. The highest value of number of leaf, flower, fruit and fruit weight gained from potassium in rate 1.5gm/L in both methods. While the highest value of total soluble solid (T.S.S) obtained from 3.5gm/L which was %12.87, and the highest value of T.A was significantly gained from the control which was % 0.51. As regards to interaction between soil and foliar fertilizer, the highest number of leaf was gained from control  at foliar application without  any significant value with  the other rates, and the highest significant value in number of flower was gained from 1.5gm at foliar application. While the highest value of fruit weight was gained from foliar application with 3.5gm and soli fertilizer with 1.5gm of potassium without any significant value between the two treatments which are 21.72gm and 20.12gm successively, and the highest significant value of total acidity was gained from control at foliar application which is %0.54. As regards to total soluble solid the highest significant value was obtained from 3.5gm in soil fertilizer which is %14.25.